2005
DOI: 10.1200/jco.2005.02.147
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Phase II Study of Cetuximab in Combination With Carboplatin in Patients With Recurrent or Metastatic Nasopharyngeal Carcinoma

Abstract: Cetuximab in combination with carboplatin demonstrates clinical activity and an acceptable safety profile in heavily pretreated patients with recurrent or metastatic NPC who had previously experienced treatment failure with platinum-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
167
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(175 citation statements)
references
References 29 publications
4
167
2
2
Order By: Relevance
“…Another phase 2 trial tested it in combination with cetuximab, a targeted therapy against epidermal growth factor receptor which is expressed in most NPCs, in patients who had progressed on or within 12 months after termination of platinum based chemotherapy for recurrent or metastatic NPC. This trial yielded a response rate of 11.7% and the authors concluded that this combination demonstrated clinical activity with an acceptable toxicity profile in a heavily pretreated population (Chan et al, 2005). More recently, carboplatin has been compared to CDDP in the definitive setting with chemoirradiation for locally advanced NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Another phase 2 trial tested it in combination with cetuximab, a targeted therapy against epidermal growth factor receptor which is expressed in most NPCs, in patients who had progressed on or within 12 months after termination of platinum based chemotherapy for recurrent or metastatic NPC. This trial yielded a response rate of 11.7% and the authors concluded that this combination demonstrated clinical activity with an acceptable toxicity profile in a heavily pretreated population (Chan et al, 2005). More recently, carboplatin has been compared to CDDP in the definitive setting with chemoirradiation for locally advanced NPC.…”
Section: Introductionmentioning
confidence: 99%
“…11 EGFR monoclonal antibody, cetuximab (C225), had demonstrated a gratifying survival benefit in combination with chemotherapy or radiotherapy for NPC and other types of HNSCC. [12][13][14] Thus, to identify more novel molecular markers that not only can predict the prognosis individually but also provide promising therapy targets will be of great benefit for advanced NPC patients.…”
Section: Elevated Beclin 1 Expression Is Correlated With Hif-1α In Prmentioning
confidence: 99%
“…Due to the peculiar characteristics in its epidemiology, pathology, clinical behavior and response to treatment, NPC is different from other head and neck squamous cell cancer and has a relatively high overall survival rate with the integration of chemotherapy into radiotherapy (2,3). However, the majority of NPC patients present with a late stage disease accompanying neck nodal metastases when diagnosed, and the cure rate for those advanced NPCs remains unsatisfactory (4). In addition, numerous NPC survivors are often affected by moderate to severe late complications, resulting from the impact of radiation on the organs that are adjacent to the nasopharynx and neck nodes, and chemotherapy in advanced cases further exacerbates these side-effects (5).…”
Section: Introductionmentioning
confidence: 99%